Elevation Shift in Abies Mill. (Pinaceae) of Subtropical and Temperate China and Vietnam—Corroborative Evidence from Cytoplasmic DNA and Ecological Niche Modeling - Shao, Yi-Zhen; Zhang, Xian-Chun; Phan, Loc Ke; Xiang, Qiao-Ping (Frontiers in Plant Science, 2017)
The “elevational shift” scenario has been proposed as a model to explain the response of cold-adapted organisms to Quaternary climatic fluctuations in Europe and North America. However, the elevational shift model has not been well-explored in eastern Asia, which is more topographically complex than the other Northern Hemisphere biogeographic regions. Here, we evaluated the role of elevational shift in the closely related firs, or Abies Mill., of subtropical and temperate China. These firs are typical alpine trees with sensitivity to climate change. We tested the elevational shift hypothesis in firs of China using phylogeographic methods and ecological niche models. Our phylogeographic analyses comprised mitochondrial and chloroplast polymorphisms surveyed across 479 individuals from 43 populations representing 11 species. M1of the 11 mitotypes and C1 of the 25 chlorotypes were inferred as the ancestral haplotype, and they had the widest distribution. The results of our phylogeographic survey revealed multiple centers of genetic diversity in distinct geographic regions and no latitudinal trend. Moreover, our results showed range expansions for seven taxa during the last glacial (64.9–18.2 kya or 32.5-9.1 kya), and this was consistent with the Quaternary fossil record of Abies in China. Taken together, our findings support a historical biogeographic pattern in firs of glacial expansions, probably through corridors at lower elevation, and interglacial fragmentations, through isolation at higher elevation peaks. Therefore, Abies in China probably undergoes elevational shift in response to climate change. Facing the forecasting global warming, the risk of several critically endangered firs was further enhanced as these species would have little escape space in situ to higher altitudes. According to our ENMs, we proposed an ex situ conservation strategy in the southern Hengduan Mountains region of south western China.